2021
DOI: 10.3389/fmed.2021.771206
|View full text |Cite
|
Sign up to set email alerts
|

Novel CircRNAs in Hub ceRNA Axis Regulate Gastric Cancer Prognosis and Microenvironment

Abstract: Gastric cancer (GC) is one of the most prevalent malignancies with an unfavorable survival rate. Immunotherapy may contribute to a better prognosis. However, several phase III trials failed. Circular RNA (circRNA) is a novel type of non-coding RNA, plays a vital role in the progression of tumors. The expression and function of circRNA in the GC immune microenvironment remain obscure. In this study, we utilized a bioinformatic analysis to construct a circRNA/microRNA (miRNA)/messenger RNA (mRNA) network involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…On the other hand, the machine learning method used in this study was demonstrated three significant down-regulated miRNAs has-miR-6510, has-miR-6507, has-miR-6512 in gastric cancer which recently gained attention in gastric cancer. Li et.al showed that miR-6512 downregulated in gastric cancer patients and seems to have a correlation with skin manifestations and fibrosis 46 . Moreover, a study by Ding demonstrated that miR-6507 was among top five down expressed miRNAs in GC and may serve as a good predictive biomarker 47 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the machine learning method used in this study was demonstrated three significant down-regulated miRNAs has-miR-6510, has-miR-6507, has-miR-6512 in gastric cancer which recently gained attention in gastric cancer. Li et.al showed that miR-6512 downregulated in gastric cancer patients and seems to have a correlation with skin manifestations and fibrosis 46 . Moreover, a study by Ding demonstrated that miR-6507 was among top five down expressed miRNAs in GC and may serve as a good predictive biomarker 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that circRNAs acting as ceRNAs participate in GC progression by sponging miRNAs to regulate target genes of miRNAs. [31][32][33] Zhang et al reported that circ_HN1, miR-628-5p and Ecto-5'-nucleotidase could construct a ceRNA network to regulate GC development. 33 The circ-ITCH as a ceRNA regulated the miR-199a-5p/Klotho axis, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The competing endogenous RNA (ceRNA) hypothesis was first proposed by Salmena et al ( 13 ), who suggested that any gene containing miRNA response elements can be combined with miRNA through the miRNA response elements, thereby inhibiting the effect of miRNAs and indirectly regulating the expression of protein-coding genes. ceRNA is a cross-regulatory network that mediates malignant tumor cell phenotypes, including proliferation and inhibition, autophagy, infinite growth, induction of angiogenesis and angiogenic mimicry, and immune escape ( 14 , 15 ). Dong et al found that the lncRNA GAS5 significantly reduced ovarian cancer cell proliferation and invasion by acting as a ceRNA and suppressing miR-96-5p expression, thereby providing a therapeutic strategy for ovarian cancer treatment ( 16 ).…”
Section: Introductionmentioning
confidence: 99%